The Triangulation Blueprint: Bridging the Gap Between Rhetoric and Reality in Islamic Religious Education - Ridha Aulia; Sazkia Nazilla; Muhammad Naufal Mifta Al Ghifari; Monica Sundawati Susanto; Angga Prasetiya (Bustanul Ulum Journal of Islamic Education, 2026)
The transformation of education in the era of Independent Learning necessitates robust character development. However, affective assessment in Islamic Religious Education (PAI) often becomes limited to administrative formalities, risking the reduction of the curriculum’s vision to rhetoric without meaningful behavioral change. This study critically examines the challenges and strategies in implementing affective observation assessment at SMP Negeri 1 Baitussalam, Aceh Besar. Employing a qualitative case study, data were gathered through observation, documentation, and in-depth interviews with PAI teachers and students. Analysis utilized Krathwohl’s Affective Taxonomy and Character Education Theory. Findings indicate that value internalization is hindered by subjectivity bias, students’ psychological barriers to honest self-reflection, social conflicts in peer-assessment, and the “name passenger” phenomenon in group tasks. Instrument triangulation—integrating self-assessment, peer assessment, and teacher journals—emerges as an effective strategy, minimizing data manipulation and fostering internalization of values. This triangulation model is recommended as an authentic standard to strengthen character education in the digital era.